An Approach to Sustaining Future Ready Curriculum Implementation in Higher Education - Dayang Nur Salmi Dharmiza, Awang Salleh; Nur Tahirah, Razali; Anna, Andrew; Devagi, Kanakaraju; Adibah, Yusuf; MUHAMAD FADZLI, ASHARI (2025)
Teaching and learning (T&L) in higher education is facing new challenges in the 21st century, resulting in the need to adapt to current situations and emerging requirements. The Future Ready Curriculum (FRC) elements were introduced to equip students with essential future skills to meet the demands of dynamic job markets and evolving global challenges. Universiti Malaysia Sarawak (UNIMAS) has established targets and strategies for tracking FRC implementation across undergraduate programmes to examine its scalability, feasibility, and effectiveness. This study analyses the annual achievement of FRC element implementation, specifically in transformative T&L delivery and alternative assessment, from 2021 to 2025 across STEM and non-STEM programmes. The achievement was measured by the percentage of core courses implementing the FRC elements, with targets gradually increasing each year—from 50% in 2021 to 80% in 2025—to ensure steady progress. Over the years, most programmes showed a consistent increase in implementation, achieving the annual targets. Initially, seven out of ten faculties met the target with minor exceptions. By 2025, all programmes reached the 80% threshold, indicating the potential for sustainability in FRC implementation. This study concludes that systematic, data-driven target setting supports sustainable large-scale reform adoption in higher education, despite the lack of qualitative measures. Future research should explore the pedagogical impacts and effects on student learning outcomes.